UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI LINGKARAN DENGAN MENERAPKAN DISCOVERY LEARNING - Rubiyati, Rubiyati (Jurnal Inovasi Pembelajaran di Sekolah, 2022)
Based on the background of the problems described above, several problems can be identified as follows: students are less able to master Mathematics learning in class VI even semester of SD Negeri Tlogosari Kulon 03. Of the 40 children only 16 children (40.00%) reached the KKM. The teacher's efforts to improve the ability of learning outcomes in the material "Circle" by using Discovery Learning in the sixth grade students of the even semester of SD Negeri Tlogosari Kulon 03 Semarang. This research uses the type of CAR (classroom action research), carried out at SD Negeri Tlogosari Kulon 03 Pedurungan District, Semarang City in October – November 2019. The subjects of this class action research are: Class VI students, totaling 40 students. The results showed: (1) Learning by using Discovery Learning can improve student learning outcomes in the "Circle" Material for Class VI Mathematics at SD Negeri Tlogosari Kulon 03 Kec. Pedurungan Semarang City which is marked by an increase in student learning outcomes in each cycle, namely pre-cycle 63.50; the average of the first cycle is 72.70 and the second cycle is 82.10; (2) Learning using Discovery Learning can improve student learning outcomes in the "Circle" material for Class VI Mathematics at SD Negeri Tlogosari Kulon 03 Kec. Pedurungan Semarang City which is characterized by an increase in student learning outcomes in each cycle, namely pre-cycle 40.00%; in the first cycle increased to 62.50% and the second cycle reached 87.50%. The conclusion of this research is that student learning outcomes and learning mastery in Mathematics lessons on the "Circle" material can be increased by applying Discovery Learning to students of class VI Semester 1 SD Negeri Tlogosari Kulon 03 Pedurungan District, Semarang City for the 2019/2020 academic year.